Sikap Peduli Lingkungan Siswa SMPN Adiwiyata Tingkat Provinsi Di Banjarmasin Utara - Norlinda Norlinda; Parida Angriani; Muhammad Muhaimin; Karunia Puji Hastuti; Sidharta Adyatma (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
The Adiwiyata school program has a concept to encourage all school members to form a life behavior that is more concerned about the environment. Environmental care attitude is one of the attitudes that must be applied in the school environment at every level of education. The purpose of this study was to determine the attitude of Adiwiyata SMPN students toward environmental care at the provincial level in North Banjarmasin. The research method used is quantitative, with data collection techniques through observation, questionnaires, and documentation. The population in this study were all VIII grade students: SMPN 13, SMPN 15, SMPN 21, SMPN 24, and SMPN 27 Banjarmasin City—sampling using the Proportional Random Sampling technique. The sample amounted to 290 respondents. The results showed that implementing the Adiwiyata program made students more aware and concerned with the environment. This is evidenced by the calculation results, averaging 91.79 in the caring category. Some students can form an awareness of environmental conditions. Students at school can save water by using the hand-washing water tap provided by the school. Be good at energy management by turning off electronic devices when not in use, turning off lights during the day, and utilizing sunlight as a source of lighting in the classroom.